Association between the BDNF Val66Met Polymorphism and Chronicity of Depression - Lee, Yujin; Lim, Shinn Won; Kim, Soo Yeon; Chung, Jae Won; Kim, Jinwoo; Myung, Woojae; Song, Jihae; Kim, Seonwoo; Carroll, Bernard J; Kim, Doh Kwan (Psychiatry investigation, 2013)
Both clinical and biological factors influence the course of depressive disorders. This study tested for associations between the brain-derived neurotrophic factor (BDNF) gene at the Val66Met locus and the course of major depressive disorder (MDD). Three hundred ten Korean subjects (209 patients, 101 controls) were genotyped for rs6265 at nucleotide 196 (G/A), which produces an amino acid substitution at codon 66 (Val66Met) of the gene for BDNF. Course of illness was evaluated both by chronicity of current episode (episode duration >24 months) and by the lifetime history of recurrences. Patients with the Met/Met BDNF genotype had a significantly higher rate of chronic depression than all others. There was a significant dose effect of the Met allele on chronicity. Compared with the Val/Val genotype, the relative risk of chronicity was 1.67 for the Val/Met genotype, and 2.58 for the Met/Met genotype. Lifetime history of recurrent episodes was not related to BDNF genotypes but was significantly associated with younger age of onset and with a history of depression in first degree relatives. BDNF genotyping may be informative for anticipating chronicity in major depression.